Polycaprolactone/organoclay biodegradable nanocomposites: Dissimilar tendencies of different clay modifiers - Ollier Primiano, Romina Paola (2018)
In this work, biodegradable nanocomposites based on polycaprolactone (PCL) reinforced with 2.5, 5.0 and 7.5 wt.% of two different clays, a commercial organo-clay (Cloisite 20A, C20A) and a laboratory modified bentonite with tributylhexadecyl phosphonium bromide (bTBHP), were prepared by melt intercalation followed by compression molding. The study contemplates the analysis of chemical (Infrared Spectrometry, FTIR), morphological (X-Ray Diffractometry, XRD, Scanning Electron Microscopy, SEM, and Transmission Electron Microscopy, TEM), rheological, thermal (Differential Scanning Calorimetry, DSC, and Thermogravimetrical Analysis, TGA) and mechanical properties (tensile tests), which are important properties for packaging applications. In previous works, we concluded that higher clay dispersion degree inside the PCL matrix is expected when clays with large interlayer distance, strong hydrophobicity and strong processing stability are used. In the present work the opposite result was obtained. Although the phosphonium treated clay (bTBHP) showed the largest interlayer distance (d001), strongest hydrophobicity and the best processing stability, the clay dispersion degree inside PCL was worse than in the case of the alkylammonium treated clay (C20A). PCL/bTBHP nanocomposites showed weaker mechanical properties in comparison with PCL/C20A ones, which is in accordance with the morphological analysis. On the other hand, the thermal properties of the matrix were not substantially affected by clay incorporation in both nanocomposites.